2021
DOI: 10.3389/fimmu.2021.694318
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Sphingolipid Profile Associated With Subclinical Atherosclerosis and Clinical Disease Markers of Systemic Lupus Erythematosus: Potential Predictive Value

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that affects females more than males, with African Americans developing more severe manifestation of the disease. SLE patients are at increased risk for cardiovascular disease (CVD), and SLE women 35-44 years old have 50 fold the incidence rate of CVD. Because SLE patients do not follow the typical age and gender pattern for CVD, but instead an accelerated disease course, the traditional biomarkers of elevated LDL and total cholesterol levels d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
(70 reference statements)
3
14
0
Order By: Relevance
“…Among them, glucosylceramide and SM levels were also associated with SLE disease score ( Supplementary Figure 6B ). Consistently, sphinganine and SM were reported to be changed in SLEs and related to complications, thus supporting our data ( 20 ). These data show the potential value of assessing sphingolipid changes in SLEs, especially in the HA group, and supports the use of sphingolipidomics as a tool to pinpoint a biomarker for early identification ( 12 ).…”
Section: Resultssupporting
confidence: 92%
“…Among them, glucosylceramide and SM levels were also associated with SLE disease score ( Supplementary Figure 6B ). Consistently, sphinganine and SM were reported to be changed in SLEs and related to complications, thus supporting our data ( 20 ). These data show the potential value of assessing sphingolipid changes in SLEs, especially in the HA group, and supports the use of sphingolipidomics as a tool to pinpoint a biomarker for early identification ( 12 ).…”
Section: Resultssupporting
confidence: 92%
“…When we adopted the final extraction protocol (Materials and Methods, Section 3.4 , protocol 4), for both complex sphingolipids and sphingoid bases (long chromatography on Cortecs C18), the concentration range of the analytes fell perfectly into those described in the literature [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and the reproducibility of the methods was validated ( Table 1 and Table 2 ). In Figure 4 , the attained ranges are shown.…”
Section: Resultsmentioning
confidence: 97%
“…One of the main issues in the analysis of Sph and other sphingoid bases is that their levels in plasma and other biological matrices are not always high enough to allow a precise quantitation. Bearing in mind that the concentrations of sphingoid bases in human plasma range from 0.006 µM to 1.56 µM [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] ( Supplementary Figure S1 ), it is critical to be aware of any possible interferents in the analysis. As particularly appraisable in Figure 3 , choosing the appropriate column and chromatography conditions can make a huge difference in sphingoid bases analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, these authors observed a positive association between plasma PhE concentration (mainly equol and enterolactone) and the prevention of hypertension. Other studies, including the report from Hammad and colleagues [ 185 ] demonstrated that the usage of resveratrol during the post-menopausal period is a valid and safer alternative to Es to prevent vascular calcification. Finally, Wolters et al [ 186 ] defined the effects of PhE supplementation in postmenopausal women in a metanalysis of randomized controlled trials.…”
Section: Estrogens and Sphingolipidsmentioning
confidence: 99%